Use of andiroba oil to control Anastrepha fraterculus (Diptera: Tephritidae) in different fruit hosts. (2021)
Control of Anastrepha fraterculus (Diptera: Tephritidae) is usually accomplished with synthetic insecticides, which can be a problem considering exportation of fruits. This study aimed to evaluate mortality and offspring effects on A. fraterculus using peach, strawberry guava and apple fruits treated with andiroba (Carapa guianensis) oil. Higher mortality rate was observed when compared to control on strawberry guava and apple fruits treated with andiroba oil (18.4 % and 35.0 % points more than the control). The mean number of pupae observed in the offspring was inferior to the control on strawberry guava and apple fruits treated with andiroba oil (100 % control) and, on peach fruits (68.3 % fewer pupae). Andiroba oil shows promising results as an alternative product to control A. fraterculus. Studies are still needed especially considering the effectiveness of andiroba oil under field conditions.